Perspectiveson Low Global Interest Rates - Catao, Luis (IMF Working Papers; Working Paper ;, 2006)
This paper looks at the dramatic decline in global real interest rates in recent years from a historical perspective and examines the various factors that may account for this trend. We show that current levels of real interest rates on long-term bonds in advanced economies are not low by historical standards and that it is the real long bond rates of the early 1980s through much of the 1990s that look anomalous. We also find that current global long-term interest rates are roughly in line with what one would predict given current price-earnings (P/E) ratios and under reasonable assumptions about the equity risk premia and the expected rate of growth of earnings in advanced countries. Finally, we provide econometric evidence that global long-term interest rates are significantly affected by commodity prices, expected productivity growth, and fiscal consolidation in advanced countries.